PENGGUNAAN MEDIA GAMBAR SERI UNTUK MENINGKATKAN KEMAMPUAN MENYUSUN KALIMAT DALAM PARAGRAF PADU - Ani, Yohana; Chiar, M; Nasrun, M (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstrak: From the research results can be generally concluded that the application of RPP by using the Image Series on the learning construct coherent sentences in paragraphs Fourth grade students SDS Good Shepherd 2 East Pontianak increased improvement was evident in the first cycle of 46.33% in the second cycle increased 66.7% . (2) The implementation of learning by using the Picture Series in formulating coherent sentences in paragraphs Fourth grade students SDS Good Shepherd 2 East Pontianak in accordance with a prepared lesson plan. (3) Physical activity learning Indonesian with media Image Series in formulating coherent sentences in paragraphs Fourth grade students SDS Good Shepherd 2 Pontianak East in the first cycle of 40% less active second cycle increased to 76% is quite active and 24% are very active. (4) Mental Activity Indonesian learning by using the Picture Series in formulating coherent sentences in paragraphs Fourth grade students SDS Good Shepherd 2 Pontianak East in the first cycle of 40% less active second cycle increased to 36% is quite active and 64% are very active. (5) Activities emotional learning Indonesian with media Image Series in formulating coherent sentences in paragraphs Fourth grade students SDS Good Shepherd 2 Pontianak East in the first cycle of 40% less active second cycle increased to 76% is quite active and 24% are very active. Dari hasil penelitian secara umum dapat disimpulkan bahwa Penerapan RPP dengan menggunakan media Gambar Seri pada pembelajaran menyusun kalimat dalam paragraf padu siswa kelas IV SDS Gembala Baik 2 Pontianak Tenggara terjadi peningkatan perbaikan terbukti pada siklus I 46,33% pada siklus II meningkat 66,7%. (2) Pelaksanaan pembelajaran dengan menggunakan media Gambar Seri dalam menyusun kalimat dalam paragraf padu siswa kelas IV SDS Gembala Baik 2 Pontianak Tenggara sesuai dengan RPP yang telah disiapkan. (3) Aktivitas fisik pembelajaran Bahasa Indonesia dengan menggunakan media Gambar Seri dalam menyusun kalimat dalam paragraf padu siswa kelas IV SDS Gembala Baik 2 Pontianak Tenggara pada siklus I 40% kurang aktif siklus II meningkat menjadi 76 % cukup aktif dan 24 %sangat aktif. (4) Aktivitas Mental pembelajaran Bahasa Indonesia dengan menggunakan media Gambar Seri dalam menyusun kalimat dalam paragraf padu siswa kelas IV SDS Gembala Baik 2 Pontianak Tenggara pada siklus I 40% kurang aktif siklus II meningkat menjadi 36 % cukup aktif dan 64 %sangat aktif. (5) Aktivitas emosional pembelajaran Bahasa Indonesia dengan menggunakan media Gambar Seri dalam menyusun kalimat dalam paragraf padu siswa kelas IV SDS Gembala Baik 2 Pontianak Tenggara pada siklus I 40% kurang aktif siklus II meningkat menjadi 76 % cukup aktif dan 24 %sangat aktif.